A Simpler Standard for Small Entities - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2013)
In Singapore and many other countries around the world, laws or regulations require most small and medium-sized entities (SMEs) to publish general purpose financial statements and have them audited (typically subject to an audit exemption threshold). The rational is that stakeholders such as banks, suppliers, customers, rating agencies, venture capitalists, and outside investors all use the financial statements of SMEs to make lending, credit and investment decisions. SMEs also have incentive to provide high quality and comparable information to their stakeholders because high quality financial information will help them to reduce their cost of both debt and equity capital.